From transmission to adaptive evolution: genomic surveillance of Getah virus - Yuge Yuan; Yujia Hao; Chengcheng Peng; Duo Zhang; Duo Zhang; Wenzhou Ma; Pengpeng Xiao; Nan Li (Frontiers in Cellular and Infection Microbiology)
Getah virus (GETV) is a member of the Alphavirus of the Togaviridae. It is a single-stranded positive-RNA virus that is mainly transmitted by mosquitoes. In recent years, the spread of GETV has become increasingly serious, causing serious losses to the animal economy and posing a potential threat to public health. GETV infected animals extend from traditional domestic animals such as horses and pigs to cattle, foxes and other animals. Especially in China, the virus has been detected in many provinces in recent years. In addition, GETV-specific antibodies were detected in healthy humans. However, the threat posed by GETV in China has not received enough attention. In this study, we downloaded all available GETV genome-wide serials (82 serials in total) from the NCBI as of December 2023. We integrate multiple bioinformatics approaches to understand the characteristics of GETV from the perspectives of epidemiology, virus-host co-evolution, and viral adaptation analysis. The results of this study show that GETV is rapidly expanding its host range and geographical distribution at high evolutionary rates due to the lack of commercially available vaccines. Second, we clearly reveal the cross-species transmission of GETV. Finally, we identified important adaptive and active selection sites. GETV and its media are widely distributed in China, and new host infections continue to appear. Therefore, strengthening surveillance and prevention to avoid serious losses to the pandemic is an important task we face today.